Metabolism of 18:4n-3 (stearidonic acid) and 20:4n-3 in salmonid cells in culture and inhibition of the production of prostaglandin F2alpha (PGF2alpha) from 20:4n-6 (arachidonic acid) - Ghioni, Cristina; Porter, Alexander E A; Taylor, Graham W; Tocher, Douglas R (Springer, 2002)
Arachidonic acid (AA; 20:4n-6) is the precursor of a range of highly biologically active derivatives, collectively termed eicosanoids, including prostaglandins, thromboxanes, leukotrienes and lipoxins, that act as autocrine hormones regulating many physiological processes including haemostasis, reproduction, immune and inflammatory responses. Eicosapentaenoic (EPA; 20:5n-3) and dihomo-γ-linolenic (20:3n-6) acids modulate eicosanoid metabolism by both inhibiting the conversion of AA to eicosanoids whilst simultaneously being converted to eicosanoids with different, often attenuated, properties compared to their AA homologues. Eicosatetraenoic acid (20:4n-3) is a naturally occurring C20 polyunsaturated fatty acid (PUFA), present in fish oil at levels of around 1-2%, that has been suggested to be the active metabolite responsible for the anti-inflammatory effects of plant oils containing stearidonic acid (18:4n-3). However, the biochemical properties of 20:4n-3 in terms of cellular biology have rarely been investigated, partly due to difficulties in obtaining the fatty acid in high purity. In this paper, we describe methods for the medium scale laboratory preparation of high purity 20:4n-3, and investigate its metabolism in fish cell culture systems which normally contain significant amounts of n-3 PUFA. Thus the incorporation and metabolism of 18:4n-3 and 20:4n-3, and their distribution in phospholipid classes was studied in an established cell line from Atlantic salmon (Salmo salar) (AS), and the effects of 20:4n-3 on eicosanoid production studied in freshly isolated macrophages from rainbow trout (Oncorhynchus mykiss). Both 18:4n-3 and 20:4n-3 were preferentially esterified into phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine in contrast with the accumulation of AA in phosphatidylinositol. Incorporated 18:4n-3 was readily converted to 20:4n-3, and both fatty acids were further desaturated and elongated to EPA and 22:5n-3 but not 22:6n-3. Supplementation with 20:4n-3 decreased the conversion ...